2008
DOI: 10.1007/s10570-008-9241-5
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of the perdeuterated cellulose solvents N-methylmorpholine N-oxide (NMMO-d11 and NMMO-15N-d11), N,N-dimethylacetamide (DMAc-d9 and DMAc-15N-d9), 1-ethyl-3-methylimidazolium acetate (EMIM-OAc-d14) and 1-butyl-3-methylimidazolium acetate (BMIM-OAc-d18)

Abstract: The syntheses of several perdeuterated substances-some of them isotopically labeled ( 15 N) in addition-are described, which act as direct solvents of cellulose either on their own, such as N-methylmorpholine N-oxide (NMMO), 1-butyl-3-methylimidazolium acetate (BMIM-OAc), or 1-ethyl-3-methylimidazolium acetate (EMIM-OAc), or in combination with auxiliaries, such as N,N-dimethylacetamide (DMAc-for the cellulose solvent DMAc/LiCl). NMMO-d 11 (9) was obtained in an eight-step approach from non-labeled diglycolic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 28 publications
0
8
0
1
Order By: Relevance
“…A typical NMR spectrum of the ionic liquid samples studied is shown in Figure , which shows the 1 H NMR spectrum of the [EMIM] + cation in the [EMIM][TFSI] ionic liquid together with the peak assignment, based on the data of Adelwohrer et al . previously reported.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A typical NMR spectrum of the ionic liquid samples studied is shown in Figure , which shows the 1 H NMR spectrum of the [EMIM] + cation in the [EMIM][TFSI] ionic liquid together with the peak assignment, based on the data of Adelwohrer et al . previously reported.…”
Section: Resultsmentioning
confidence: 99%
“…[TFSI] ionic liquid together with the peak assignment, based on the data of Adelwohrer et al [18] previously reported. The 19 FNMR spectrumo ft he [TFSI] À anion,r eported in the ESI material, showedas ingle peak for the equivalent fluorinea toms in [TFSI] À ,i na greement with what has previously been reported.…”
Section: Pfg Nmr Diffusion Studies Of Neat Ionic Liquidsmentioning
confidence: 99%
“…Since proton NMR data of high resolution could only be found for neat [C 2 mim][BF 4 ], for the analysis of calculated NMR shifts the preference was given to the literature data taken in the same solvent with a relatively low dielectric constant such as chloroform, as these NMR data are expected to be the closest to those of neat samples. For the C 2 mim-based ionic liquids coupled with the tetrafluoroborate, chloride, acetate, dicyanamide, hexafluorophosphate, and ethylsulfate anions, the NMR data came from the literature data in deuterated chloroform solutions, whereas for the ILs in combination with the trifluoroacetate and tosylate anions, the proton NMR spectra were measured in this work (for more detail see Experimental Procedures).…”
Section: Resultsmentioning
confidence: 99%
“…Chemical shifts of equivalent protons in the cation (e.g., protons in the methyl groups) were found to differ by 1 ppm on average and, therefore, were calculated as an average value. In order to be consistent with the available experimental data, the 1 H NMR chemical shifts of the ion pairs were calculated with respect to the magnetic shielding value of twelve equivalent protons in tetramethylsilane (TMS). For the sake of consistency, absolute magnetic shielding of protons in TMS was calculated at the same levels of theory as those of the ion pairs. The geometry of TMS was optimized at the MP2/aug-cc-pVDZ level of theory.…”
Section: Theoretical Proceduresmentioning
confidence: 99%
“…Viele Arbeitsgruppen versuchten im Laufe des letzten Jahrhunderts die Struktur der Cellulose und deren Abbau im Detail zu verstehen. Es wurden zahlreiche Modelle zur Beschreibung der molekularen Struktur von Cellulose entwickelt [1] und unterschiedliche Wege zur Auflösung [2] oder zum Abbau der Cellulosefasern zu Polysacchariden [3] vorgeschlagen. In der letzten Zeit rücken die enzymatischen Hydrolyseverfahren zunehmend in den Mittelpunkt [4].…”
Section: Problemstellungunclassified